2017
DOI: 10.1055/s-0037-1604198
|View full text |Cite
|
Sign up to set email alerts
|

Otogenic Lateral Sinus Thrombosis: A Review of Fifteen Patients and Changing Trends in the Management

Abstract: Introduction  Otogenic lateral sinus thrombosis is a rare intracranial complication of otitis media in the modern age of antibiotic treatment, but it is potentially a dangerous complication. Objectives  The aim of this study is to focus on the various clinical presentations, management options and sequelae in a series of fifteen patients with otogenic lateral sinus thrombosis. Methods  Retrospective chart review of inpatients treated for otogenic lateral sinus thrombosis at our tertiary care institution betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…Early diagnosis and rapid treatment are crucial to improving the prognosis of this potentially lethal disease. The diagnosis is based on clinical manifestations and confirmed by imaging (5).…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis and rapid treatment are crucial to improving the prognosis of this potentially lethal disease. The diagnosis is based on clinical manifestations and confirmed by imaging (5).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of adequate antibiotic treatment, the incidence of severe complications such as Bezold abscess and LST has dramatically decreased, and simultaneous coexistence was described only in a few cases. [3][4][5] Because of the rarity of these complications, experienced radiologists and otolaryngologists are needed for the right diagnosis. The location of the ear canal dehiscence could stay hidden in a simple otomicroscopic evaluation; therefore, otoendoscopic examination can help the diagnostic efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Early use of broad-spectrum antibiotics and surgical intervention are recognized as the preferred treatment for sigmoid sinus thrombophlebitis. Common operations include 5,7,8 : radical mastoidectomy, sigmoid sinus aspiration or incision, thrombectomy, and internal jugular vein ligation. Some authors have suggested that relatively conservative surgical treatment can achieve a good prognosis, without the need to open the sigmoid sinus or remove blood clots or ligate the internal jugular vein.…”
Section: Discussionmentioning
confidence: 99%